RORA Regulates Autophagy in Hair Follicle Stem Cells by Upregulating the Expression Level of the Sqstm1 Gene - Xuefei Zhao; Yanchun Xu; Shuqi Li; Suying Bai; Wei Zhang; Yu Zhang (Biomolecules)
The hair coat is an adaptive evolutionary trait unique to mammals, aiding them in adapting to complex environmental challenges. Although some of the factors involved in regulating hair follicle development have been characterized, further in-depth research is still needed. Retinoic acid receptor-related orphan receptor alpha (RORA), as a member of the nuclear receptor family, is highly involved in the regulation of cellular states. Previous studies have shown that autophagy plays a significant role in hair follicle development. This study uses rat hair follicle stem cells (HFSCs) as a model to analyze the impact of RORA on the autophagy levels of HFSCs. Upon activation of RORA, autophagy indicators such as the LC3-II/LC3-I ratio and MDC staining significantly increased, suggesting an elevated level of autophagy in HFSCs. Following treatment with chloroquine, the LC3-II/LC3-I ratio, as well as the expression levels of BECN1 protein and SQSTM1 protein, were markedly elevated in the cells, indicating that the autophagic flux was unobstructed and ruling out the possibility that RORA activation impeded autophagy. Additionally, the level of the Sqstm1 gene increased markedly after RORA activation promoted autophagy in the cells. We found that RORA regulates the transcription level of Sqstm1 by binding to its promoter region. We believe that RORA activation significantly promotes the level of autophagy, particularly selective autophagy, in HFSCs, suggesting that RORA has the potential to become a new target for research on hair follicle development. This research provides a theoretical foundation for studies on hair follicle development and also offers new insights for the treatment of diseases such as alopecia.